Hikikomori (Severe Social Withdrawal) in Italian Adolescents: Clinical Features and Follow-Up - Greta Tolomei; Gabriele Masi; Annarita Milone; Pamela Fantozzi; Valentina Viglione; Antonio Narzisi; Stefano Berloffa (Children, 2023)
Severe social withdrawal, including staying alone in one’s bedroom, non-attendance at school or work, and minimal or absent social contacts, sometimes only through electronic devices, can be found in several psychiatric disorders, or in a ‘primary’ form, firstly defined in Japan as ‘Hikikomori’. The distinction between primary and secondary forms is questionable, as it prevalently depends on the quality of psychiatric assessment. To date, few studies specifically explored Hikikomori in an adolescent population outside Japan. The aim of the present study is to describe clinical features of a consecutive group of 80 referred youth (13 to 18 years, 57 males) with social isolation, of which 40 were followed up on for 4–6 months, to characterize clinical features and outcome. All the participants presented psychiatric comorbid disorders, prevalently anxiety disorders, mood disorders, and autism spectrum disorder. Suicidality (ideation and behavior) was reported in 32.5% of the participants, and 20% of the participants attempted suicide. More than half of the participants exceeded the cut-off of the Internet Addiction Test, and 42.4% met the criteria for the Internet Gaming Disorder. At the follow-up appointment, an improvement of social withdrawal was reported in 75% of the sample; 67.5% of the participants significantly improved according to the CGI-improvement scale; and 55% of the participants had an improvement of functioning according to the C-GAS. Our findings suggest that Hikikomori is a transnosographic entity, with high rates of suicidality and Internet addiction, and that can it improve when it is timely diagnosed and treated.